2019
DOI: 10.1177/2156759x20912750
|View full text |Cite
|
Sign up to set email alerts
|

Validation of High School Students’ Scores on the Revised Fit, Stigma, and Value Scale: Implications for School Counseling Screening

Abstract: We tested the dimensionality of the Revised Fit, Stigma, and Value (FSV) Scale, a screening instrument for assessing barriers to counseling among a national sample of 330 students from 260 high schools across 45 states. Results supported the three-dimensional FSV model and the presence of a second-order factor. Based on the findings, we present implications for enhancing school counselors’ universal screening of barriers and how it impacts comprehensive school counseling program efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…An emergent body of literature has demonstrated moderate-to-strong internal consistency reliability evidence for scores on the Approach/Encourage and Diminish/Avoid subscales of the MDRS with samples of 4-year university students (α = .70, α = .84; Kalkbrenner & Flinn, 2020), community college students (α = .76, .84; Kalkbrenner, Goodman-Scott, & Neukrug, 2020), and faculty members (α = .73, α = .70; Kalkbrenner, 2020a). Past investigators had found strong construct validity evidence for the MDRS via confirmatory factor analysis (CFA; Kalkbrenner & Flinn, 2020) and multiple-group CFA (Kalkbrenner, 2020b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An emergent body of literature has demonstrated moderate-to-strong internal consistency reliability evidence for scores on the Approach/Encourage and Diminish/Avoid subscales of the MDRS with samples of 4-year university students (α = .70, α = .84; Kalkbrenner & Flinn, 2020), community college students (α = .76, .84; Kalkbrenner, Goodman-Scott, & Neukrug, 2020), and faculty members (α = .73, α = .70; Kalkbrenner, 2020a). Past investigators had found strong construct validity evidence for the MDRS via confirmatory factor analysis (CFA; Kalkbrenner & Flinn, 2020) and multiple-group CFA (Kalkbrenner, 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…The MDRS is a mental health literacy-based screening tool (see instrumentation section below) for appraising students’ two primary responses (i.e., approach/encourage and diminish/avoid) when encountering a peer in mental distress. The MDRS was normed with two large samples of undergraduate college students (Kalkbrenner & Flinn, 2020) and the generalizability of the MDRS’s psychometric properties are promising: Past investigators confirmed its dimensionality with samples of faculty members (Kalkbrenner, 2020a) and community college students (Kalkbrenner, Goodman-Scott, & Neukrug, 2020). If scores on the MRDS are validated with high school students, the MDRS has implications for addressing the aforementioned gap in the literature surrounding mental health literacy-based UMHS tools for promoting peer-to-peer mental health support at the high school level, with the overarching goal of school counselors better supporting students’ mental health as part of implementing a comprehensive program.…”
Section: Peer-to-peer Mental Health Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…A second tool, the MDRS, measures how college students respond to a peer who is experiencing mental distress, such as referring them to a counseling center (Kalkbrenner & Flinn, 2020). The FSV and the MDRS are two important screening tools that can be used to identify students who can benefit from psychoeducation sessions focused on mental health awareness (Kalkbrenner & Flinn, 2020; Kalkbrenner et al., 2020; Wei et al., 2015). Specifically, the practical utility of the FSV and MDRS scales includes campus‐wide screening that produces results for informing the content of MHL‐based psychoeducation sessions (Kalkbrenner & Flinn, 2020; Kalkbrenner et al., 2020).…”
Section: Hispanic Serving Institutions and Unique Mental Health Needsmentioning
confidence: 99%
“…To summarize, mental health screening is one method of understanding the reasons why college students do not attend counseling and can lead to the development of targeted strategies for increasing MHL, harm‐prevention through early identification, and positive views concerning mental health treatment (Kalkbrenner et al., 2019). To this end, college counselors at HSIs need easy‐to‐use screening tools with validated scores that can identify barriers to seeking counseling, such as the Revised FSV Scale and the MDRS (Kalkbrenner & Flinn, 2020; Kalkbrenner & Neukrug, 2018, 2019; Kalkbrenner et al., 2020). Despite the emergent body of literature in support of the psychometric properties of the MDRS and Revised FSV Scale with a number of different populations, scores on the MDRS and Revised FSV Scale have not been validated with HSI students.…”
Section: Hispanic Serving Institutions and Unique Mental Health Needsmentioning
confidence: 99%